Postcolonial Brazil - Weinstein, Barbara (The Oxford Handbook of Latin American History, 2010)
This article is a portal into the rapidly expanding historiography of modern Brazil. It highlights the major nodes of discussion and debate among historians of Brazil over the last two decades, and describes how these debates have been shaped by broader shifts in the historical profession. Two themes frame this survey of the new historiographical trends for postcolonial Brazil. One is the impact of the linguistic or cultural turn on that historiography. Slower to have an impact in the Brazilian historiography were the writings of the Subaltern Studies scholars and postcolonial theorists.
Keywords: 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice